1996
DOI: 10.1073/pnas.93.1.201
|View full text |Cite
|
Sign up to set email alerts
|

The estrogen receptor locus is associated with a major gene influencing litter size in pigs.

Abstract: Identification of individual major genes affecting quantitative traits in livestock species has been limited to date. By using a candidate gene approach and a divergent breed cross involving the Chinese Meishan pig, we have shown that a specific allele of the estrogen receptor (ER) locus is associated with increased litter size. Female pigs from synthetic lines with a 50% Meishan background that were homozygous for this beneficial allele produced 2.3 more pigs in first parities and 1.5 more pigs averaged over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
236
2
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 311 publications
(253 citation statements)
references
References 28 publications
10
236
2
5
Order By: Relevance
“…However, the sampling error is not the only cause that explains the diversity found in the results of the literature. While Rothschild et al [47] and Short et al [49] found differences for all traits, Southwood et al [52] did not find a significant effect of the B allele in NBA and TNB. This lack of significance was mainly due to a second parity drop, which had its largest effect impact in the more productive genotypes [52].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…However, the sampling error is not the only cause that explains the diversity found in the results of the literature. While Rothschild et al [47] and Short et al [49] found differences for all traits, Southwood et al [52] did not find a significant effect of the B allele in NBA and TNB. This lack of significance was mainly due to a second parity drop, which had its largest effect impact in the more productive genotypes [52].…”
Section: Discussionmentioning
confidence: 94%
“…Standard errors originally not reported and computed in this work to make meta-analysis possible are over or underestimated. For example, for Korwin-Kossakowska et al [26], Rothschild et al [47], Short et al [49] and Southwood et al [52] standard errors were overestimated when the differences were significant, since they represent the maximum standard error inferred by the level of significance reported. And, oppositely, when differences were not significant, standard errors were underestimated, since they represent the minimum standard error inferred by the level of significance reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations